Florence Nightingale: the impact of her contributions in the contemporary world of nursing - Anelise Miritz Borges; Cristiele Berthold; Katiuscia Milano Rosales de Rodrigues; Sonia Maria Könzgen Meincke; Marilu Correa Soares; Roxana Isabel Cardozo Gonzáles (Universidad de Alicante, 2012)
The role of caring is part of human existence and is related to the woman's image that has sought, through this practice, a form of survival that has evolved into broader areas such as promotion and health maintenance. Objective: To reflect on the contributions of Florence Nightingale for the care exercise in the current days. Methodology: It is a reflective study with historical perspective, structured by themes, whose sources of data collection were journal articles, books, and critical works approached in the Nursing Academic Master. Results: Florence Nightingale became the character that retracts the nursing profession through their worldview, becoming a benchmark of life and professional practice in this area of health. Conclusions: We found that her theoretical vision contributed to the demystification of disparities related to gender, favoring the exercise of the intellectual capacity of women in society. She has received this merit through her scientific knowledge, giving an organized profile to the class. Her care was recommended to the human being and directly associated to his environment, expressions of a holistic work, pre-announcing the definition that includes the individual totality in the field of nursing.